Rapid decarbonization requires industrial efficiency - Yang, Miying; Evans, Steve (Springer, 2025)
The potential of effciency to support decarbonization is underestimated and overlooked relative to more expensive and intensive actions. Implementing resource and energy effciency strategies in industry could deliver rapid and cost-effective decarbonization.
Keywords: 33 Built Environment and Design; 41 Environmental Sciences; 3302 Building; 7 Affordable and Clean Energy